DBS handbook of dron technology - Khandelwal, K K; Sisai, Deep Sihag (New Delhi DBS Imprints, 2025)
Drone technology, or unmanned aerial vehicle (UAV) technology, encompasses the design, development, and operation of remote-controlled or autonomous flying devices. Drones have transformed industries like aerial photography, surveying, mapping, agriculture, and package delivery. Equipped with sensors, GPS, and cameras, they capture high-resolution images, collect data, and navigate challenging environments. Advances in drone technology have enhanced stability, maneuverability, and flight duration. Increasing adoption is revolutionizing tasks like infrastructure inspection, disaster response, and environmental monitoring. Innovations in drone technology are expected to unlock new possibilities and applications across various sectors, improving efficiency, safety, and productivity. With growing demand, drones are becoming essential tools in many fields, offering unparalleled versatility and flexibility. As technology continues to evolve, the potential applications of drones are vast and exciting, promising to transform the way we work and live.
Keywords: Dron Technology; IAS as Author